2021
DOI: 10.1108/intr-03-2020-0158
|View full text |Cite
|
Sign up to set email alerts
|

Group polarisation among location-based game players: an analysis of use and attitudes towards game slang

Abstract: PurposeThis study investigates how game design, which divides players into static teams, can reinforce group polarisation. The authors study this phenomenon from the perspective of social identity in the context of team-based location-based games, with a focus on game slang.Design/methodology/approachThe authors performed an exploratory data analysis on an original dataset of n = 242,852 messages from five communication channels to find differences in game slang adoption between three teams in the location-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 67 publications
0
27
0
Order By: Relevance
“…However, such TB does not occur in all games. For example, recent work with players of Pokémon GO and Ingress showed that members of certain teams developed prejudices and negative feelings toward opposing team members with whom they were in conflict [50], but not toward members of the same team. This difference suggests that constantly changing teams (as in LoL and Dota 2) increase TB towards teammates, while static teams (as in Pokémon GO) decrease TB as teammates get to know and trust each other.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…However, such TB does not occur in all games. For example, recent work with players of Pokémon GO and Ingress showed that members of certain teams developed prejudices and negative feelings toward opposing team members with whom they were in conflict [50], but not toward members of the same team. This difference suggests that constantly changing teams (as in LoL and Dota 2) increase TB towards teammates, while static teams (as in Pokémon GO) decrease TB as teammates get to know and trust each other.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Gathering open online data has the benefit over surveys and interviews that there is no research setting influencing and exerting bias to the data [14]. Instead, open online data can capture users' authentic reactions [15]. The YouTube comment section has been deemed a fairly reliable source of information, although not representative of the global population [16].…”
Section: Data Sources -Youtubementioning
confidence: 99%
“…The extant literature on sociality in Pokémon GO is outlined in Table 2. There exists a wide range of studies related to social interaction in Pokémon GO, discussing both offline and online social gameplay [35,55]. Early on in 2016, shortly after the launch of Pokémon GO, sociality did not seem to motivate players to play the game [54].…”
Section: Socialization In Pokémon Gomentioning
confidence: 99%
“…At the same time, there is strong evidence that Pokémon GO was able to activate players [31,63], bring players to physical proximity to meaningfully cooperate with one another [11], increase their social connectedness [64] and to even influence the language and slang preferences of players [35].…”
Section: Socialization In Pokémon Gomentioning
confidence: 99%
See 1 more Smart Citation